Elasto-plastic shear behavior of reinforced honeycomb and auxetic reentrant lattices - Vitor Carneiro; José Meireles (Millenium, 2018)
Introduction: Auxetic materials possess a negative Poisson’s ratio. Even though, the existence of isotropic auxetics is theoretically possible, they seem to be absent in natural states thus, there has been an effort to produce artificial auxetics mostly by the design of inverted (reentrant) honeycombs.